Effect of Surface Density on the Fire Performance of Wood and Wood-Based Materials - Anita Firmanti; Subyakto Subyakto; Bambang Subiyanto; Shuichi Kawai (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
Surface density known as mass per unit area or as a product of density and thickness was analyzed as a key factor in predicting the fire performance of wood and wood based materials. Sawn timber of Mangium (Acacia mangium Willd) and Gmelina Arborea (Gmelina arborea Roxb.) in various thicknesses, manufactured particleboards and cement bonded particleboards of both species in various densities and thicknesses were used as the testing materials. Commercial particleboards, cement bonded particleboards and MDF were also tested. Boards were tested under ISO 5660 using cone calorimeter. Physical and mechanical properties were tested based on ASTM and JIS standards. The physical and mechanical properties of manufactured wood based panels could fulfil the JIS standard. Ignition time is affected by the surface density and effective surface area to the heat exposure of the boards. Boards reacted in different ways to the heat exposure but they needed similar time to the critical temperatures of 260 °C, in the similar surface density regardless of materials type. Surface density could be used as a key parameter in the fire resistant design process. The results of tested boards under ISO 5660 were about two third of those under JIS A 1304.Key words: cone calorimeter, fire resistant performance, surface density, wood, wood based materials.